Radio serving the rural areas of the ACP-countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Support for rural radio is an integral part of CTA's communication development strategy. This directory, compiled from questionnaire information, interviews and existing guides and directories, provides details on rural radio stations in 71 ACP countries.